2005
DOI: 10.1002/pd.1090
|View full text |Cite
|
Sign up to set email alerts
|

Accepting or declining the offer of prenatal screening for congenital defects: test uptake and women's reasons

Abstract: The uptake of prenatal screening was relatively low, and different distributions of reasons were reported, compared to other studies. These differences may be due to the specific Dutch situation in which prenatal screening is not part of standard prenatal care. The question arises as to whether informed decision-making would be reduced if prenatal screening became routinised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 34 publications
3
80
2
2
Order By: Relevance
“…In The Netherlands, these aspects have indeed been shown to be reasons for declining prenatal screening. 6,21 Participants were therefore very positive about NIPT, as they thought that the characteristics of the test, that is, the increased accuracy, reduced chance of requiring follow-up testing and earlier performance could diminish the disadvantages of prenatal screening and thus lower the barrier for participation. These findings are in line with other studies where positive attitudes and high interest in NIPT were found among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In The Netherlands, these aspects have indeed been shown to be reasons for declining prenatal screening. 6,21 Participants were therefore very positive about NIPT, as they thought that the characteristics of the test, that is, the increased accuracy, reduced chance of requiring follow-up testing and earlier performance could diminish the disadvantages of prenatal screening and thus lower the barrier for participation. These findings are in line with other studies where positive attitudes and high interest in NIPT were found among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Greely 5 , for example, provides a summary of the ethical questions that have been raised with regard to the implications of NIPT on the current prenatal screening setting and even on society as a whole. 5 Where many women now decline prenatal screening due to the miscarriage risk of follow-up diagnostic testing, 6 it is likely that more women will consider NIPT as it does not jeopardise the health of their foetus. Ethicists, however, worry that the safety and ease of the test might lead to normalisation of testing (trivial to offer and take) and to a decrease in informed choice, as parents might not be aware or fully comprehend what they are consenting to.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Another explanation might be that these participants were of the opinion that the screening test was not good enough, as research has shown that many women give this reason ("unfavorable test characteristics") for declining prenatal screening. 34 On the other hand, value inconsistency due to accepting prenatal screening while being negative about it might be attributed to social pressure or normalization of prenatal screening. Further research is needed to investigate the real causes behind value inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…7 Sadece hastaların %5,8'i (n=18) inancım nedeniyle test yaptırmak istemiyorum şeklinde cevap vermiştir. Bu grubun tamamı ikili ve üçlü tarama testleri için bu cevabı vermiştir.…”
Section: 5unclassified